Protectionism vs. Non-Interventionism: Two Approaches to Media Diversity in Commercial Terrestrial Television Regulation - Ohlsson, Jonas; Sjøvaag, Helle (Javnost-The Public, 2019)
Roughly a decade has now passed since the full-scale introduction of digital terrestrial television (DTTV) across the European continent. In Scandinavia, DTTV put an end to the so-called duopolistic television market model, in which a fee-financed public service broadcaster (PSB) competed with a commercial, but carefully regulated, broadcaster—a hybrid. The hybrid concept was an attempt to maintain a diverse broadcasting market also in small linguistic markets. Building on the theoretical framework of market failure, this article compares the impact on external and internal market pluralism of the protectionist policy of Norway, which has chosen to keep a hybrid channel also in the new multi-channel environment, and the non-interventionist policy of Sweden, in which the hybrid concept has been abandoned. The results point to a problematic trade-off, where the more public service-oriented Norwegian hybrid TV2 has experienced plummeting market shares, whereas the Swedish “former-hybrid” TV4—following a clear reorientation towards more market-oriented programming—has been able to uphold theirs. The findings highlight the increasing difficulties of designing effective national media policies in the globalised media landscape.